The System of Sources of Islamic Law - A. M. Magomedov (Московский журнал международного права, 2011)
The article deals with the system of sources of Islamic law in its historical development and its possibility of applying acts of the international law in Muslim countries. Special attention is paid to the Islamic legal doctrine and its influence on the formation of international legal regulation of social relations in the Islamic countries. Islam can be treated as universal outlook, containing its own concepts of culture, politics and rights, including an original perspective on the construction of legal system different from Europe, whose experience could be useful for the development of world-wide legal system. A key feature that distinguishes the Islamic law from other legal systems is the reliance on the moral authority of the Muslim religion and the basis of its legitimacy are not public service, but divine will. The main interest in a practical sense provides the final part of the article concerning the transformation of Islamic law in national legal systems.